1995
DOI: 10.1136/gut.36.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the intragastric distribution of Helicobacter pylori during treatment with omeprazole.

Abstract: MethodsPatients attending for routine diagnostic gastroscopy and likely to need omeprazole were invited to take part in, and give written consent to this study, which was approved by the Parkside Ethical Committee. Patients with previous gastric surgery, known bleeding diathesis, taking oral anticoagulants, or who had been treated with bismuth compounds, omeprazole, or antibiotics known to be active against H pylori within the previous two months, were excluded. To determine H pylori status biopsy specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
169
1
11

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(197 citation statements)
references
References 18 publications
13
169
1
11
Order By: Relevance
“…Although the in¯uence of omeprazole on the mucosa of the body of the stomach was transient, those who underwent subsequent maintenance treatment with H 2 -blockers showed a persistent increase in neutrophil in®ltration in the body of the stomach. These results corresponded with those reported by Logan et al 23 and Solcia et al 24 who investigated changes in H. pylori-related fundal or corpus gastritis using omeprazole, and reported that omeprazole improves antral H. pylori gastritis and worsens the fundal or corporal gastritis, and suggested that even H 2 -blockers, a weaker acid secretion inhibitor, Figure 6. The effect of acid secretion inhibitors on the amount of H. pylori, IL-8 content and neutrophil in®ltration in the body of the stomach in DU patients.…”
Section: Discussionsupporting
confidence: 90%
“…Although the in¯uence of omeprazole on the mucosa of the body of the stomach was transient, those who underwent subsequent maintenance treatment with H 2 -blockers showed a persistent increase in neutrophil in®ltration in the body of the stomach. These results corresponded with those reported by Logan et al 23 and Solcia et al 24 who investigated changes in H. pylori-related fundal or corpus gastritis using omeprazole, and reported that omeprazole improves antral H. pylori gastritis and worsens the fundal or corporal gastritis, and suggested that even H 2 -blockers, a weaker acid secretion inhibitor, Figure 6. The effect of acid secretion inhibitors on the amount of H. pylori, IL-8 content and neutrophil in®ltration in the body of the stomach in DU patients.…”
Section: Discussionsupporting
confidence: 90%
“…19 Hence, we speculate that the reduction in H. pylori gastritis in the antrum after treatment with omeprazole is associated with a direct antibacterial activity of omeprazole against H. pylori that reduces its density in the antrum, 20,21 or alternatively, the shift in the distribution of H. pylori gastritis towards the corpus correlates with the respective drug's ef®cacy in increasing the pH. This means that a proton pump inhibitor may reduce the acid output to such an extent that H. pylori can only survive in the corpus close to the acidproducing parietal cells where the pH value remains low enough for its survival, 9 whereas ranitidine or antacids increase the pH enough to allow an increase in H. pylori gastritis in the corpus, but not to suppress H. pylori gastritis in the antrum. That the increase in the in¯ammation in the corpus is pH-related rather than being a direct toxic effect of the respective drug is also supported by studies showing similar results after proximal selective vagotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest scenario is where patients undergo endoscopy and biopsies while on continued therapy with proton pump inhibitors or antibiotics. 41 A false-negative histology result can also occur where there is extensive gastric atrophy and intestinal metaplasia.…”
Section: Invasive Testsmentioning
confidence: 99%